Penerapan Model PBL Berbasis Permainan Edukatif untuk Meningkatkan Kemampuan Penyelesaian Masalah Matematika Kelas 1C SDN Kauman - Safa'ah, Fitriani; Restian, Arina; Kumalasari, Ratna Nur (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to analyze the application of the Problem Based Learning (PBL) model based on educational games in improving mathematics problem solving skills in class 1C students at SDN Kauman 1 Malang City. This research approach uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results showed that the application of PBL based on educational games can significantly improve students' ability to identify, formulate, and solve mathematical problems. This model also increases motivation, participation, and critical thinking and collaboration skills among students. Educational games that are designed to help students understand mathematical concepts in a real context can also create fun and meaningful learning, in line with constructivist learning theory. Obstacles such as differences in student understanding and time constraints can be overcome with intensive assistance and simplification of the games. This study also concluded that PBL based on educational games is an innovative approach that is effective in improving problem solving skills and student engagement.